PA.50 Impact of a neonatal echocardiography clinic service in a Level 3 NICU centre. (9th June 2014) - Palanisami, B; Rakhecha, A; Gottstein, R
Abstract : Introduction: Asymptomatic cardiac murmurs are commonly detected on newborn examination. These babies are frequently referred to paediatric cardiology services. To reduce waiting time for evaluation of these neonates, a neonatologist run echocardiography clinic was set up. Aim: To analyse the cardiac disease burden and time to diagnosis of neonates referred to neonatal echocardiography clinic in a Level 3 NICU over a 2 year period. Methods: Retrospective analysis of contemporaneously collected data on infants who attended the echocardiography clinic from January 2012 to December 2013. Results: 66 neonatal echocardiography clinics were conducted. 140 patients were seen on 164 occasions. Median age 1 st seen in the clinic, days (range) 41(2–202). 159 babies were referred, 123 for murmur detected on newborn examination (Echo finding: Normal-48, PDA-5, ASD-8, VSD-29, Coarctation-1, Pulmonary stenosis-5, Fallots tetralogy-1, MR-1, TR-1, Branch PA stenosis-6, Dextrocardia-1, DNA-17), 10 with first degree relatives with coarctation (Normal-9, coarctation-1), 12 with sibling with CHD (Normal-8, PDA-1, Branch PA-stenosis-1, DNA-2) and 14 for miscellaneous indications. Cardiac pathologies were identified in 47%(66/140). Conclusion: This model worked effectively in discharging nearly half of the referrals thus decreasing the burden on tertiary paediatric cardiology services. Babies were seen earlier than would have been seen in the cardiology clinic. With experience, the referral criteria were modified in early 2013 and also more of the minor cardiac defects were followed up in this clinic rather than referred.